Evaluation of TMO’s (Turkish Grain Board) Appointment System for Procurement - Gursel Kusek (New Medit, 2018)
This study was conducted in the Konya province, which is one of the most important grain production centers of Turkey. The primary data was obtained by questionnaires that were given out to 54 producers. The main purpose of this study is investigating the effects of TMO’s “Appointment System for Procurement (ASP)” on marketing structure of wheat and the decision-making process of farmers.